Case Report: Minigene assays reveal a novel DNAAF6 intronic variant as the key etiology for primary ciliary dyskinesia - Long, Yupeng; Li, Huixian; Yu, Haoyue; Yi, Qian; Meng, Xiong; Wang, Xi; Ren, Qinqin; Ding, Dongyan; Li, Haidong; Zhang, Fenglan; Qiu, Hao; Yang, Xuemei (Frontiers in Genetics, 2025)
BackgroundPrimary ciliary dyskinesia (PCD), a rare hereditary disorder characterized by impaired ciliary motility, is frequently linked to infertility. Elucidating PCD’s genetic basis is critical for accurate diagnosis and clinical management. However, research on the pathogenicity of intronic variants in non-classical splice regions of DNAAF6—a newly identified PCD-associated gene in recent years—remains scarce.Case presentationA proband with primary ciliary dyskinesia (PCD) and male infertility underwent whole exome sequencing (WES), revealing a novel hemizygous intronic variant in the DNAAF6 gene (NM_173494.2: c.515 + 3_515+6del, Clinvar Variation ID:4075425). Sanger sequencing confirmed this variant in his affected brother. A minigene splicing assay showed that the variant caused exon six skipping, leading to a frameshift. Transmission electron microscopy (TEM) analysis of sperm flagella indicated absent outer and inner dynein arms, resulting in flagellar immotility.ConclusionThis study identifies and confirms a novel pathogenic intronic variant of DNAAF6 in a Chinese PCD family, expanding the DNAAF6 mutational spectrum. It also emphasizes the critical role of minigene-based functional validation in interpreting variants of uncertain significance (VUS).